Fatal Toxic Megacolon in a Child of Hirschsprung Disease - Garg, Shiwani R (J Clin Diagn Res, 2016)
Hirschsprung disease (HD) in late childhood is uncommon and often undiagnosed or misdiagnosed. However, in a patient with Hirschsprung disease, of greater significance is the occurrence of life threatening enterocolitis. In its more severe form, this is associated with gross dilatation of the colon and profound toxaemia, the combination being termed toxic megacolon. Because of its relative rarity, we report a case of 10-year-old child who had a history of chronic constipation for nine years. He later developed complications and presented to the emergency department with toxic megacolon, a rare occurrence due to neglected constipation. Though patient’s condition was unstable, laparotomy with right transverse colostomy was performed after appropriate intravenous rehydration. The dilated bowel loops were decompressed and intraoperatively multiple site biopsies were done. Histopathological examination of transition zone biopsy revealed absence of ganglion cells suggestive of Hirschsprung disease. But few hours later patient’s condition worsened and he succumbed.